Skin-effect influence on transition radiation - Miroshnichenko, V.I.; Ostroushko, V.M. (Вопросы атомной науки и техники, 2015)
It is considered the transition radiation for the normal incidence of a charged particle on the boundary of plasma medium in the conditions of anomalous skin effect, at the frequencies much less than plasma frequency. The problem is solved in the assumption that electron scattering from the boundary is partially specular and partially diffusive. The spectral density of the radiated energy is obtained for the cases of uniform particle motion and of the motion with two running across the boundary.